Efficacy, safety and pharmacokinetics of a new 10% normal human immunoglobulin for intravenous infusion, BT595, in children and adults with primary immunodeficiency disease. Issue 10 (9th August 2022) - Kriván, Gergely; Borte, Michael; Harris, James B.; Lumry, William R.; Aigner, Silke; Lentze, Stephan; Staiger, Christiane
Abstract: Background and Objectives: To evaluate the efficacy, safety and pharmacokinetics of a new, highly purified 10% IVIg (BT595, Yimmugo®) administered in children and adults with Primary immunodeficiency diseases (PID). Materials and Methods: Prospective, uncontrolled, multicentre Phase III trial. Patients aged 2 to <76 years with PID were switched from their pre‐trial IVIg replacement therapy to BT595. In all, 67 patients (49 adults, 18 children) received doses between 0.2 and 0.8 g/kg body weight for approximately 12 months at intervals of 3 or 4 weeks. Dosing and dosing intervals were based on each patient's pre‐trial infusion schedule. The primary end point was the rate of acute serious bacterial infections (SBIs); secondary efficacy, safety and pharmacokinetic outcomes were also evaluated. Results: The primary efficacy end point was met, and the unadjusted SBI rate was 0.01 per subject‐year (adjusted SBI rate 0.015 per subject‐year, with an upper limit of the one‐sided 99% confidence interval of 0.151). A single adult patient experienced one event classified as an SBI. All secondary end points, including those related to infections, supported the efficacy. Infusion rates were increased up to 8 ml/kg/h. Overall, 8% of infusions were associated with ≥1 infusional adverse event (AE) (start during or within 72 h post‐infusion), comprising mainly headache (2.4%), fatigue (0.9%) and nausea (0.5%). There were no infusional AEs at infusion rates of >4.0 ml/kg/h, and only one patient required a single premedication. The observed patterns, severity and frequency of treatment‐emergent adverse events are consistent with the established safety profile for IVIgs and did not show clinically relevant differences between all age groups. Conclusion: BT595 is effective, safe and well tolerated for treating patients with PID.